17 Puppy adventures [videorecording (DVD)] (PBS Kids, 2023)
"Everyone loves dogs, including your favorite PBS KIDS friends! In a special collection, Arthur's dog Pal takes advantage of the special treatment he gets when he has to wear a cone. Pinkalicious helps her friend train his dog for the Pinkminster Dog Show. And Tooey must choose a puppy to train as a sled dog. Plus, Alma recruits her friends and their pets for an animal show, the Kratt brothers go to India to find the Dhole, aka "The Red Dog" and many more canine capers!" --